0270 Lipid Peroxidation Parameters In Menopausal Women Of The Two Ethnic Groups With Insomnia. (12th April 2019) - Semenova, Natalya; Madaeva, Irina; Kolesnikova, Lyubov
Abstract: Introduction: 35-60% of menopausal women complain about certain problems with sleep. It is well known, that sleep loss may cause oxidative stress. At the present time, it is known that lipid peroxidation processes in both healthy individuals and in pathological conditions have ethnospecificity. The aim of this work was assessment of the lipid peroxidation processes in Caucasian (ethnic group - Russian) and Asian (ethnic group - Buryat) menopausal women with insomnia. Methods: 181 menopausal women divided into Caucasian (n=91) and Asian (n=90) groups were examined. All women underwent clinico-anamnestic examination. Polysomnography and specialized questionnaires for the assessment of sleep disorders were used. Each ethnic group was divided into control (with insomnia) and main group (with insomnia). Lipid peroxidation parameters (conjugated dienes (CDs), malonyl dialdehyde (MDA)) by spectrophotometric methods were determined. Results: In Caucasian patients compared to control was observed accumulation of lipid peroxidation products both in perimenopause (CDs) (by 25% (р<0.05)) and in postmenopause (CDs, MDA) (by 42% and 21% respectively (р<0.05)). Also, a higher content of CDs (by 37% (р<0.05)) in perimenopause and MDA (by 51% (р<0.05)) in postmenopause in Asian patients compared to control was found. Conclusion: Our results demonstrate the development of oxidative stress in patients with insomnia in both Caucasian and Asian menopausal women. Support (If Any): No